Improving powerlifters’ technical preparedness at initial training stage using a device for remote control of competitive exercises technique - Власов, А.; Панарін, Б.; Розторгуй, М.; Товстоног, О. (Physical Education Theory and Methodology, 2016)
The objective is to improve powerlifters’ technical preparedness at the initial training stage using a device for remote control of the competitive exercises technique. Materials and methods. The study relied on the following methods used: theoretical analysis and collation of data of scientific and methodological literature and internet; pedagogical observation; pedagogical experiment; methods of mathematical statistics. Results. We have designed an algorithmic structure for teaching squats with a barbell on shoulders in powerlifting and a device for remote control of the competitive exercises technique. We used the pedagogical experiment and pedagogical observation of the competitive activity to reveal reliable deviations (p > 0.05) in the number of mistakes made by the athletes of the reference and experimental groups during the competitive activity. The reference group powerlifters made the mistake “no straight angle between the knee and the hip joints when performing the third stage” twelve times, while the experimental group athletes — seven times. Conclusions. The results obtained allow to maintain that the experimental group athletes have more rationally mastered the competitive exercises technique and made fewer mistakes compared to the control group powerlifters. This confirms the effectiveness of the designed algorithmic structure for teaching squats with a barbell on shoulders.